Detection of herpes simplex virus in direct specimens by immunofluorescence assay using a monoclonal antibody. - Pouletty, P (1987)
A monoclonal antibody (MAb), designated CHA 437, was developed against herpes simplex virus (HSV). This MAb (isotype, immunoglobulin G2b K) reacted with HSV type 1 and HSV type 2. It showed no cross-reactivity with varicella-zoster virus, cytomegalovirus, or Epstein-Barr virus. Direct detection of HSV antigen in clinical specimens using indirect immunofluorescence with this MAb was compared with tissue culture isolation. For the 682 specimens tested, the direct specimen test gave a sensitivity of 84.6% and a specificity of 95.7%.